2015
DOI: 10.1002/bab.1354
|View full text |Cite
|
Sign up to set email alerts
|

Effects of even and odd number fatty acids cofeeding on PHA production and composition in Pseudomonas putida Bet001 isolated from palm oil mill effluent

Abstract: The biosynthesis of medium-chain-length poly-3-hydroxyalkanoates by Pseudomonas putida Bet001 cultivated on mixed carbon sources was investigated. The mixed carbon sources consisted of heptanoic acid (HA) and oleic acid (OA). A relatively low PHA content at 1.2% (w/w) and 11.4% (w/w) was obtained when HA or OA was used as the sole carbon source. When these fatty acids were supplied as a mixture, PHA content increased threefold. Interestingly, the mixture-derived PHA composed of both odd and even monomer units,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Culture condition is one of the main factors that affects the production of PHA. Various types of mcl‐PHA monomeric composition can be synthesized by providing different carbon sources in the cultivation medium . In this study, mcl‐PHA was produced through fed‐batch fermentation process by P. putida BET 001.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture condition is one of the main factors that affects the production of PHA. Various types of mcl‐PHA monomeric composition can be synthesized by providing different carbon sources in the cultivation medium . In this study, mcl‐PHA was produced through fed‐batch fermentation process by P. putida BET 001.…”
Section: Resultsmentioning
confidence: 99%
“…Purification steps were repeated three times by dissolving the PHA in acetone followed by re‐precipitation in cold methanol. The PHA composition and its cellular content were analyzed using gas chromatography (GC) . The extracted mcl‐PHA composed of three different monomers viz .…”
Section: Methodsmentioning
confidence: 99%
“…Most mcl-PHAs with saturated monomers exhibit single-step degradation in the temperature range 255−350 • C. Incorporating monomers with a longer alkyl chain has increased T d [45,53]. Razaif-Mazinah et al [40] stated that a unique monomer distribution and shorter monomeric chain lengths resulted in a lower T d . Still, the variation is only in a narrow range (275−283 • C).…”
Section: 41mentioning
confidence: 99%
“…After isolating the biomass from the culture broth by centrifugation or filtration, the harvested cells are either freeze‐dried [ 61 , 62 ] or oven‐dried [ 40 ]. Several studies have shown that biomass should be pre‐treated to weaken the cell membrane and promote cell lysis.…”
Section: Downstream Processingmentioning
confidence: 99%
See 1 more Smart Citation